ANALYSIS OF FACTORS OF SUCCESS AND FAILURE OF MERGER ACQUISITION - Yunita; Hendri Maulana; Filya Fatriasari; Amri Sirait; Robi Sanjaya; Indrayani; Muammar Khaddafi (PT. Radja Intercontinental Publishing, 2023)
Based on previous research and phenomena, researchers will analyze the success and failure factors of mergers and acquisitions in order to gain a deeper understanding. The purpose of this research is to find out the factors that contribute to success and failure in the process of mergers and acquisitions. The research method used is qualitative research with descriptive analysis techniques, using library research. This study aims to describe current and past phenomena in the context of mergers and acquisitions, the results of the research show that the implementation of strict and comprehensive due diligence is an important factor in achieving success in conducting M&A. Organizational culture was identified as an important catalyst influencing the success rate of M&A. that strong and strategic leadership, including transformational leaders.